2015
DOI: 10.1590/0034-7167.2015680411i
|View full text |Cite
|
Sign up to set email alerts
|

Apoio social frente à necessidade de cuidado após infarto do miocárdio

Abstract: social support follows the infarction trajectory, which attains the family members and favors the support according to the needs of care in each lived moments by the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…The bulk of the literature have highlighted the importance of social support in post-MI survivors; having fragmented or fragile social support networks inhibits fundamental coping mechanisms to overcome unexpected psychosocial repercussions like chronic stress, fast-paced life, having too much responsibilities, accumulation of unpredicted life events, depression, anxiety, social isolation, and withdrawal and life chaos [ 13 , 31 , 34 ]. In this study, multivariate analysis showed that the association between concerns shown by others (emotional social support) and life chaos could not be considered as an independent association; therefore, adding an interaction without a main effect could not be considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bulk of the literature have highlighted the importance of social support in post-MI survivors; having fragmented or fragile social support networks inhibits fundamental coping mechanisms to overcome unexpected psychosocial repercussions like chronic stress, fast-paced life, having too much responsibilities, accumulation of unpredicted life events, depression, anxiety, social isolation, and withdrawal and life chaos [ 13 , 31 , 34 ]. In this study, multivariate analysis showed that the association between concerns shown by others (emotional social support) and life chaos could not be considered as an independent association; therefore, adding an interaction without a main effect could not be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In Malaysia, CVDs—particularly MI and its related complications—have topped the nation’s mortality rate, followed by deteriorating mental health outcomes [ 12 ]. With elevated anxiety and concerns, survivors of myocardial infarction and their families are often helpless in the face of new demands, adaptation, and changes in their life routines to cope with consequences of the illness [ 13 ]. These vulnerabilities influence the coping mechanisms, resulting in disarray in family routines [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can impact the personal relationships and sexual activity that are aspects evaluated in the Social Relations domain of the WHOQOL scale. During the occurrence of AMI and also in the recovery period there is strong social support, but this decreases over time [43] which may contribute to a lower perception of QoL in this domain. Another aspect is that the functional capacity of patients and the extent of cardiac involvement are also determinants of QoL in CD [8].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Houve aceitação dos familiares, por entenderem o problema e se conscientizarem da importância das mudanças. Esses achados corroboram com o elevado nível de apoio por parte das famílias, prevalecendo um suporte efetivo (38,39) . É nítido nos relatos o suporte positivo advindo do núcleo familiar, em especial da esposa, assumindo o papel de realizar as mudanças alimentares necessárias e de cobrar dos entrevistados o seguimento apropriado das orientações médicas.…”
Section: Envolvimento E Suporte Familiarunclassified